Community Sponsorship in Europe: Taking Stock, Policy Transfer and What the Future Might Hold - Tan, Nikolas Feith (Frontiers in Human Dynamics, 2021)
This article explores the recent emergence of community sponsorship of refugees in Europe, an approach which shares responsibility between civil society and the state for the admission and/or integration of refugees. Originally a Canadian model developed to support the resettlement of Indochinese refugees, the model has gained momentum in Europe, with a number of states piloting or establishing community sponsorship schemes. This proliferation, while generally seen as positive for international protection of refugees, has led to conceptual confusion and a significant range of approaches under the ‘umbrella’ concept of community sponsorship. As a result, community sponsorship today may be understood both as a form of resettlement and a complementary pathway to protection. While interest and momentum around community sponsorship is high, little work currently exists mapping and analysing how jurisdictions adopt community sponsorship model. With reference to existing work on policy transfer, this contribution takes stock of community sponsorship models in Europe; analyses how community sponsorship may become a viable policy option in European states as a form of transnational policy transfer; and sets out a number of challenges for the future development of community sponsorship in Europe.